Tabel Prediksi Moyers dan Sitepu terhadap Lebar Mesiodistal Gigi Permanen Pengganti pada Etnis Arab Yaman di Surabaya - Firyal Baktir; Dwi Prijatmoko; Masniari Novita (UPT Percetakan dan Penerbitan Universitas Jember, 2020)
There are several methods of analizing tooth size discrepancy in orthodontics include prediction methods for mixed dentition. Prediction method of Moyers and Sitepu most commonly used although both were obtained from 2 different races, Caucasian and Deutromelayu. Yemeni ethnic is one of the ethnic groups settled in Indonesia which descendants of the Caucasian race. The aim of the study was to observed the suitable prediction table for Yemeni ethnic. It was an observasional analitics study consist of 40 samples with cross sectional design. The results showed that slight difference for prediction of Moyers on the maxilla (1.02) and prediction of Sitepu on the mandibula (0.11). As conclusion, the most suitable predicition method for Yemeni ethnic is Moyers’s method for maxila and sitepu’s method for mandibula. Key words: mesiodistal width permanen teeth, Moyers method, Sitepu method, Yemeni Etnic